Venovenous Extracorporeal Membrane Oxygenation Candidacy Decision-Making: Lessons and Hypotheses From a Single-Center Observational Analysis - Rubin, Jonah; Witkin, Alison S; Crowley, Jerome C; Michel, Eriberto; Furfaro, David M; Teijeiro-Paradis, Ricardo; Ilg, Annette; Seethala, Raghu; Zhao, Sophia; Fan, Eddy (Chest, 2024)
Use of venovenous extracorporeal membrane oxygenation (ECMO) is increasing, but candidacy selection processes are variable and subject to bias. What are the reasons behind venovenous ECMO candidacy decisions, and are decisions made consistently across patients? Prospective observational study of all patients, admitted or outside hospital referrals, considered for venovenous ECMO at a tertiary referral center. Relevant clinical data and reasons for candidacy determination were cross-referenced with other noncandidates and candidates and were assessed qualitatively. Eighty-one consultations resulted in 44 noncandidates (54%), 29 candidates (36%; nine of whom subsequently underwent cannulation), and eight deferred decisions (10%). Fifteen unique contraindications were identified, variably present across all patients. Five contraindications were invoked as the sole reason to deny ECMO to a patient. In patients with three or more contraindications, additional contraindications were cited even if the severity was relatively minor. All but four contraindications invoked to deny ECMO to a patient were nonprohibitive for at least one other candidate. Contraindications documented in noncandidates were present but not mentioned in 21 other noncandidates (47%). Twenty-six candidates (90%) had at least one contraindication that was prohibitive in a noncandidate, including a contraindication that was the sole reason to deny ECMO. Contraindications were proposed as informing three prognostic domains, through which patterns of inconsistency could be understood better: (1) irreversible underlying pulmonary process, (2) unsurvivable critical illness, and (3) clinical condition too compromised for meaningful recovery. ECMO candidacy decisions are inconsistent. We identified four patterns of inconsistency in our center and propose a three-domain model for understanding and categorizing contraindications, yielding five lessons that may improve candidacy decision processes until further research can guide practice more definitively.